Fiscal Policy Response to Scaled-Up Aid. (Policy Papers; Policy Paper ;, 2007)
Sound fiscal policies are critical for handling aid volatility as well as for making effective use of scaled-up aid and other flows. By easing resource constraints, these flows allow low-income countries (LICs) to increase spending aimed at enhancing growth and reducing poverty. Effective management of these policies, however, presents a host of macroeconomic challenges, many of them fiscal.